Familial complex chromosome rearrangement ascertained by in situ hybridisation. Issue 2 (February 1997) - Fuster, C; Miguez, L; Miró, R; Rigola, M A; Perez, A; Egozcue, J
Abstract : A complex familial chromosome translocation has been ascertained by combining classical cytogenetics and CISS (chromosomal in situ suppression). Cytogenetic analysis of a chorionic villus sample with G banding showed a 47, XX, -2, +der(2)t(2;22), +der(22)t(2;22) karyotype. Analysis of peripheral blood lymphocytes from the parents by G banding and CISS showed a more complex translocation in the father: 46, XY, -2, -11, -22, +der(2) t(2;11)(q13;q23), +der(11) t(11;22) (q23;q11.2), +der(22) t(2;22) (q13;q11.2). Definitive analysis of cultured amniotic fluid cells showed a double partial trisomy of chromosomes 11 and 22. The couple decided to continue the pregnancy. The fetal karyotype was confirmed at birth. Clinical abnormalities present in our patient were typical of an unbalanced 11;22 translocation. Our findings confirm that chromosome painting techniques allow a better characterisation of complex chromosome rearrangements which may be difficult to detect in G banded karyotypes.